Analysis of Student Satisfaction on Student ID Card Making Services - Putri, Asti Ganisya Seruni; Samsuddin, Samsuddin (Borong Newinera Publisher, 2025)
This study aims to determine student satisfaction with the service of making student ID cards at Muhammadiyah University of Pontianak. This study uses the SERVQUAL method, an empirical method in analyzing services in order to improve the quality of Student Affairs services. Data collection was carried out using a questionnaire. The sample in this study amounted to 100 respondents from 14 departments at Muhammadiyah University of Pontianak. The results of this study indicate that the services available at BAAK Muhammadiyah University of Pontianak include Student Affairs Services and academic services that can be accessed according to student needs, with the percentage of services that have been channeled according to female gender with a percentage of 61% and Male gender 33% who have received services provided by the university.